Global perspectives on human capital in early childhood education : reconceptualizing theory, policy, and practice - Lightfoot-Rueda, Theodora; Peach, Ruth Lynn (New York, NY : Palgrave Macmillan, 2015)
'Global Perspectives on Human Capital in Early Childhood Education examines the emergence and global dominance of human capital theory in early childhood education. Lightfoot-Rueda, Peach, and their contributors explore the idea of human capital theory to develop children as future workers, and how this thinking shapes early childhood education policy around the globe. Early childhood educators are not yet used to thinking of their responsibilities for developing future human resources, with the standards-based curriculum, testing, and accountability in current schooling practices. Using a variety of theoretical orientations and methodologies to question whether school should be viewed mainly in terms of investment and returns, the authors look beyond the language of human capital to explore other ways we might understand schooling beyond imparting skills to future workers.'--
'Human capital theory, developing children as future workers, shapes thinking about early childhood education policy around the globe. International contributors problematize this thinking and offer alternatives'--
Machine generated contents note: -- PART I: THEORY AND HISTORY OF HUMAN CAPITAL -- 1. Introduction and Historical Perspective; Theodora Lightfoot-Rueda and Ruth Lynn Peach -- 2. Theorizing Dialogue Among Various Voices in Critical Theory; Joseph Zanoni -- PART II: DECONSTRUCTION AND CRITIQUE OF HUMAN CAPITAL AND EDUCATION -- 3. Governing the Brain: New Narratives of Human Capital in Australian Early Childhood Education; Zsuzsa Millei -- 4. The Instrumentality of Spanish in Early Spanish Education: Unraveling the Linguistic Masquerade; Alejandro Azocar -- 5.'Abilities-Machines': Human Capital Theory and Early Education by Sabiha Bilgi -- 6. Human Capital Theory and Shifting Perceptions of Teachers in the US; Theodora Lightfoot-Rueda -- 7. Reforming Early Childhood Education as a Smart Investment for the Future: Stories from East Asia; I-Fang Lee, Chao-Ling Tseng, and Hong-Ju Jun -- 8. England's Foundation Stage Child in a Shifting World: Troubling the Grids of Reasoning of'Children with Potential,''Normalization' and'Value-Added' Curriculum; Ruth Lynn Peach -- 9. Deconstructing Human Capital Discourse in Early Childhood Education in Indonesia; Vina Adriany and Kurniawan Saefullah -- PART III: RECONCEPTUALIZING EDUCATION OUTSIDE OF HUMAN CAPITAL LANGUAGE -- 10. And You Gotta Believe Me: When Social Capital and Human Capital Collide; Janice Kroeger -- 11. Questioning the Discourses of Human Capital in Early Childhood Education: Reconceptualizing Theory, Policy and Practice; Emma Buchanan -- 12. Expanding the Value of Early Education: The Capabilities Approach as an Alternative to Human Capital Theory; Cary Buzzelli -- 13. Concluding and Moving Forward; Theodora Lightfoot-Rueda and Ruth Lynn Peach.
Includes bibliographical references and index.
Keywords: Early childhood education -- Cross-cultural studies; Child development -- Cross-cultural studies; Human capital -- Cross-cultural studies